Fortification of local fruit parijoto on soy yogurt drink and economy analysis - Akhsanitaqwim, Yochidamai; Arista, Nor Isnaeni Dwi; Septiyanto, Arifin (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: The food and beverage industry is a leading industry that is the government's focus in the Industrial Revolution 4.0. Culinary is the most popular economic sub-sector.. As a food product from biotechnology, yoghurt always manages to occupy a global market share. Yoghurt is proven to maintain the digestive system. Therefore innovation is needed, especially regarding materials, to boost product competitiveness. Animal milk substrate can be substituted with soy milk which is cheap but rich in protein. The addition of natural fortification is projected to improve product quality. Parijoto fruit (Medinilla speciosa) typical of the slopes of Mount Muria, Colo Village, Kudus Regency, Indonesia was chosen as a fortificant because it is rich in antioxidants and antibacterial pathogens. At the same time, this adds to the usability and economic value of Parijoto, which is still low so far. Method: The research was conducted experimentally, referring to previous research methods. The formulation design was varied regarding adding Parijoto fruit extract to 100 ml of the product. Findings: From the results of the organoleptic test, the F1 formula (addition of 5 ml of Parijoto fruit extract) received the best acceptance from the panellists, with a preference level of 4.89. The product characteristics are liquid texture, alcoholic sweet taste, cream colour, and the aroma of Parijoto fruit tends to be faint. Conclusion:Parijoto Yogurt has advantages in terms of locality, price and nutrition. However, further research is needed based on more collaboration to increase this product's health and economic impact on local society. Novelty/Originality of this article: This study creates new functional food products and opens up opportunities to revitalize local economies and conserve biodiversity.